Trace gas fluxes of CO2, CH4 and N2O in a permanent grassland soil exposed to elevated CO2 in the Giessen FACE study - C. Müller; M. Kaleem Abbasi (Atmospheric Chemistry and Physics, 2011)
Long-term field observations showed that N2O fluxes observed shortly after N application were not significantly affected by elevated CO2 in the Giessen Free Air Carbon dioxide Enrichment (FACE) study. To further investigate this unexpected result a 15N tracer study was carried out under controlled conditions where in parallel treatments either the NH4+ pool (15NH4NO3) or the NO3− pool (NH415NO3) was enriched with 15N. Fluxes of CO2, CH4, and N2O as well as the 15N enrichment of the N2O were measured. Denitrifying Enzyme Activity (DEA), total denitrification (N2 + N2O) and N2-to-N2O ratios were quantified in separate experiments. Over the 57 day incubation, N2O fluxes averaged 0.090 ng N2O-N g−1 h−1 under ambient and 0.083 ng N2O-N g−1 h−1 under elevated CO2 (not significantly different). The N2O production processes were identified by a two-source model. Results showed that N2O must have also been produced by a third source – possibly related to organic N transformation – which was stimulated by elevated CO2. Soil CO2 fluxes were approximately 20 % higher under elevated CO2 than soil from ambient but the differences were not significant. CH4 oxidation rates were on average −1.75 ng CH4-C g−1 h−1 in the elevated and −1.17 ng CH4-C g−1 h−1 in the ambient indicating that elevated CO2 increased the CH4 oxidation by 49 % compared to ambient CO2 under controlled conditions. N fertilization increased CH4 oxidation by 3-fold in both CO2 treatments. CO2 did not have any significant effect on DEA while total denitrification and N2-to-N2O ratios increased by 36 and 33 %, respectively. The results indicate that shortly after N application elevated CO2 must have stimulated both the N2O production and reduction to N2 to explain the increased N2-to-N2O ratio and at the same time explain the non-responsiveness of the N2O emissions. Thus, the observed variation of the CO2 effect on N2O emissions throughout the year is possibly governed by the dynamics of the N2O reductase activity.